Simulation and Analysis of Distributed Generation Installation on a 20 kV Distribution System Using ETAP 19.0 - Arnawan Hasibuan; Firwan Dani; Asran; I Made Ari Nrartha (Indonesian Scientific Journal, 2022)
Conventional power plants are generally designed on a large scale, centralized, and built far from the load center so that they require transmission and distribution networks to distribute electric power. The condition of the distribution channel's length, the high load supplied, and the increasing number of requests for electrical energy each year affect the quality of distribution of electrical energy. From the above problems, simulation and analysis of the installation of distributed generation are carried out. In installing Distributed Generation, three scenarios are used based on the most significant voltage drop point. The installation of Distributed Generation scenario 1 has an average voltage value of 95.16% or 19.81 kV and an average voltage drop of 9.82% or 1.965 kV, and power losses of 946.69 Kw, where losses power loss was reduced by 17.8% or 733.7 kW. The installation of Distributed Generation scenario 2 has an average voltage value of 95.84% or 19.17 kV and an average voltage drop of 4.16% or 0.833 kV, and power losses of 1062.4 Kw, where losses power loss was reduced by 15.8% or 618 kW. The installation of Distributed Generation scenario three does not experience a voltage drop, the average voltage value is 102.4% or 20.38 kV, and power losses are 1062.4 KW, where power losses are reduced by 29.7% or 1114, 6 kW.